Effect of adding insulin degludec to treatment in patients with type 2 diabetes inadequately controlled with metformin and liraglutide: a double‐blind randomized controlled trial (BEGIN: ADD TO GLP‐1 Study). Issue 7 (2nd May 2016) - Aroda, V. R.; Bailey, T. S.; Cariou, B.; Kumar, S.; Leiter, L. A.; Raskin, P.; Zacho, J.; Andersen, T. H.; Philis‐Tsimikas, A.
Abstract : Aim: To evaluate the efficacy and safety of adding insulin degludec (IDeg) to treatment in patients with type 2 diabetes receiving liraglutide and metformin and qualifying for treatment intensification because of inadequate glycaemic control. Methods: In this 26‐week, double‐blind trial, patients who still had inadequate glycaemic control after a 15‐week run‐in period with initiation and dose escalation of liraglutide to 1.8 mg in combination with metformin (≥1500 mg) were randomized to addition of once‐daily IDeg ('IDeg add‐on to liraglutide' arm; n = 174) or placebo ('placebo add‐on to liraglutide' arm; n = 172), with dosing of both IDeg and placebo based on titration guidelines. Results: At 26 weeks, the mean change in glycated haemoglobin level was greater in the IDeg add‐on to liraglutide arm (−1.04%) than in the placebo add‐on to liraglutide arm (−0.16%; p < 0.0001). Similarly, the mean fasting plasma glucose reduction was greater, and self‐measured plasma glucose values were lower at all eight time points, with IDeg add‐on versus placebo add‐on (both p < 0.0001). At 26 weeks, the IDeg dose was 51 U (0.54 U/kg). During the run‐in period with liraglutide, body weight decreased by ∼3 kg in both groups. After 26 weeks, the mean change was +2.0 kg (IDeg add‐on to liraglutide) and −1.3 kg (placebo add‐on to liraglutide). Confirmed hypoglycaemia rates were low in both groups, although higher with IDeg than with placebo (0.57 vs. 0.12 episodes/patient‐years of exposure; p = 0.0002). Nocturnal confirmed hypoglycaemia was infrequent in both groups, with no episodes of severe hypoglycaemia, and no marked differences in adverse events with either treatment approach. Conclusion: The addition of liraglutide and IDeg to patients sub‐optimally treated with metformin and liraglutide and requiring treatment intensification was found to be effective and well‐tolerated.